Sweetpotato silage manual for smallholder farmers. - Kabirizi, J.M.; Lule, Peter M.; Ojakol, J.F.; Mutetikka, D.; Naziri, D.; Kyalo, Gerald; Mayanja, S.; Lukuyu, Ben A. (2017)
This sweetpotato silage manual is made to benefit farmers and business entrepreneurs that would want to engage in sweetpotato silage making, marketing and use. It is based on practical experiences that were gained from studies and experiments conducted in Uganda by the International Potato Centre (CIP) and the International Livestock Research Institute (ILRI) in collaboration with other partners between 2014 and 2016. The manual focused on the piggery enterprise and covers five key aspects: importance of sweetpotato in small-scale farming systems, sweetpotato establishment and management, pig production in Uganda, sweetpotato as a feed resource for pigs, sweetpotato silage production. It is expected that the manual will give the reader incites for sweetpotato production and making sweetpotato silage to address feeding constraints.